Influence - M.A. Hegazy; A.M. Badawi; S.S. Abd El Rehim; W.M. Kamel (Egyptian Journal of Petroleum)
The synthesized cationic surfactant N-(2-(2-mercaptoacetoxy) ethyl)-N,N-dimethyldodecan-1-aminium bromide (QSH) was used to prepare colloidal copper nanoparticles (CuNPs) in water through the chemical reduction method. The obtained copper nanoparticles were characterized by FTIR spectrum and transmission electron microscopy (TEM). The corrosion performance was evaluated using potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) measurements in addition to the salt spray test. The results obtained from these methods were in good agreement. Results showed that the modified coating provide a good coverage and an additional corrosion protection of the carbon steel.